2017
DOI: 10.3892/mmr.2017.6959
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between secreted protein acidic and rich in cysteine protein expression and the prognosis of postoperative patients exhibiting esophageal squamous cell carcinoma

Abstract: The aim of the present study was to investigate the association between the expression level of secreted protein acidic and rich in cysteine (SPARC) and the prognosis of postoperative patients with esophageal squamous cell carcinoma (ESCC). The expression level of SPARC was detected in the 89 ESCC tissue cases and 100 healthy esophageal mucosa cases, which served as the controls. Immunohistochemistry and reverse transcription‑polymerase chain reaction (RT‑PCR) were employed to evaluate the SPARC expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our previous work revealed that SPARC was mainly expressed in GCAFs in gastric cancer. However, most evidence supporting the role of SPARC in solid tumours is based on cancer cell-derived SPARC [1719]. SPARC derived from different cellular origins is reported to be highly heterogeneous, and SPARC expressed by different cells may even lead to opposite clinical outcomes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work revealed that SPARC was mainly expressed in GCAFs in gastric cancer. However, most evidence supporting the role of SPARC in solid tumours is based on cancer cell-derived SPARC [1719]. SPARC derived from different cellular origins is reported to be highly heterogeneous, and SPARC expressed by different cells may even lead to opposite clinical outcomes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the number of patients in each study ranged from 36 to 1,093, and a total of 5,939 patients from 11 countries were included in the present meta-analysis. The studies focused on solid tumors, including gastric cancer,11,16-18 esophageal squamous cell carcinoma,19,20 pancreatic cancer,8,21-25 lung cancer,10,26,27 breast cancer,4,9,28 colorectal cancer,29-32 diffuse large B-cell lymphoma,12,33 biliary tract cancer,7 and nasopharyngeal carcinoma 34. The positive rates of SPARC varied among the 9 solid tumors, and in the same tumor type, the positive rates of SPARC expressed in cancer and stromal cells were also different ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…SPARC becomes a prominent target for esophageal cancer imaging (Zhao et al, 2022). SPARC is linked to unfavorable prognosis in patients with ESCC (Wu et al, 2017). SPARC has a strong correlation with MMP-2 expression, and this correlation could play a critical role in the growth of esophageal cancer (Yamashita et al, 2003).…”
Section: Regulatory Mechanism Of Sparc In Esophageal Cancermentioning
confidence: 99%